Effect of using Fly Ash and Attapulgite Lightweight Aggregates on Some Properties of Concrete - Abdulhussein F.K.; Beddu S.; Nazri F.; Al-Hubboubi S.; Aljalawi N. (Dr D. Pylarinos, 2025)
Attapulgite is a natural clay mineral, that has been investigated as a potential lightweight aggregate due to its low density and unique structural properties. Recently, the interest in using attapulgite has increased. In this study, the combined attapulgite (fine and coarse) is used in a concrete mixture. Tests were conducted to select the best content of attapulgite in mixtures by investigating its properties, including slump, compressive strength, and density characteristics to evaluate Lightweight Concrete (LWC) performance. The outcomes exhibited that different attapulgite aggregate contents influence compressive strength, with the highest value being 21 MPa for 984 kg/m3 attapulgite content at 28 days of curing. Furthermore, the dry density is positively correlated with the increment of the attapulgite aggregate percentage. Then, different percentages of Superplasticizer (SP) of 0.9%, 1.1%, 1.3%, 1.5%, and 1.7% were utilized, which led to the enhancement of the slump flow. The ideal ratio adopted for the subsequent mixtures was 1.3% by weight of cementitious material, which gave the highest compressive strength (26.2 MPa at 28 days). Also, mixtures in which cement was replaced by fly ash of 10%, 20%, 30%, 60%, and 100% ratio by weight of cement were prepared. The results demonstrated that the highest compressive strength was 32.7 MPa with a 30% ratio of fly ash by weight of cementitious materials after 90 days of curing. ? by the authors.